Future of privacy and security – the Four Horsemen. Issue 4 (2nd October 2017) - Basu, Choton
ABSTRACT: In this article, the author focuses on four key issues that are expected to impact the future of privacy and security. These have been labeled — the Four Horsemen, for obvious reasons. In our assessment, these topics or "horsemen" have the potential to change the fundamental tenets of our society. They impact our banking system, medical breakthroughs, use of the internet and web-enabled devices and services. Together, these topics touch the entire range of technical, regulatory, social, legal, and commercial issues. The Four Horsemen are Net Neutrality (and U.S. Internet Privacy Laws), Internet of Things (IoT), Human Genome (Medical), and Cryptocurrency.